Proton pump inhibitors for prophylaxis of nosocomial upper gastrointestinal bleeding: the impact of standardized guidelines on prescribing practice - Yachimski, Patrick (2010)
BACKGROUND: Proton pump inhibitors (PPI) are frequently prescribed for prophylaxis of nosocomial upper gastrointestinal bleeding (UGIB). Some inpatients receiving PPI may be without risk factors for nosocomial UGIB, and PPI may be continued unnecessarily at hospital discharge. AIM: To assess the impact of standardized guidelines on PPI prescribing practices. Methods: Guidelines for PPI use were implemented on the medical service at a tertiary center. We reviewed PPI use among inpatient admissions during the month prior to implementation of guidelines then prospectively evaluated PPI use among admissions during the month following implementation of guidelines. RESULTS: 49% of patients (458/942) received PPI while inpatient, and 41% of patients (387/942) were prescribed PPI at discharge. Univariate predictors of inpatient PPI use included age, length of stay, history of GERD or UGIB, outpatient PPI use, outpatient aspirin use, and outpatient glucocorticoid use. Among patients not on outpatient PPI at admission, implementation of guidelines resulted in lower rates of inpatient PPI use (27% pre- vs 16% post-guidelines, P=0.001) and PPI prescription at discharge (16% pre- vs. 10% post-guidelines, P=0.03). CONCLUSIONS: Introduction of standardized guidelines resulted in lower rates of PPI use among a subset of hospital inpatients and reduced the rate of PPI prescriptions at hospital discharge.